Judicial Settlement of Legislative Electoral Disputes in Algerian Legislation - Djimli , Meroua; Rikli , seddik (Journal of Human Sciences, 2025)
The legislative electoral disputes are considered among the most important administrative disputes because they are closely linked to granting authority and achieving democracy, which requires protecting it from all imbalances and ensuring transparency, here the necessity of intervention by the judicial system in the electoral processes is evident to protect the various parties involved in the elections. The pivotal role of judiciary appears in the preparatory process for the legislative elections, as well as in the stage of voting and announcing the results legislative elections. As well as in the stage of voting and announcing the result through judicial settlement of disputes, that may arise in this stage, which grants voters and candidates the right to litigate to ensure the integrity of the elections.